2017
DOI: 10.5152/tud.2017.24638
|View full text |Cite
|
Sign up to set email alerts
|

Flouroscopy-free technique is safe and feasible in retrograde intrarenal surgery for renal stones

Abstract: Objective: The aim of this study was to present outcomes of our patients who had undergone retrograde intrarenal surgery (RIRS) with fluoroscopy-free technique and evaluate the efficacy and safety of the technique. Material and methods:Between January 2013 and June 2015 the outcomes of 93 patients who had undergone RIRS with fluoroscopy-free technique were retrospectively evaluated. Our RIRS technique involved preoperative assessment of ureter by semi-rigid ureteroscope, inserting guidewire through semi-rigid … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
6
0
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 20 publications
2
6
0
2
Order By: Relevance
“…In the present study, the SFR was 90.37% after 6 weeks of intervention. This finding is proportionate to comparable studies that determined the SFR of 65%–92% [2] , [39] , [40] , [41] , [42] , [47] , [48] , [49] , [50] . Moreover, the results were related to stone size; the highest SFR (100%) was achieved in stones <10 mm, and the lowest SFR (77.7%) in stones >30 mm ( p =0.0005).…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…In the present study, the SFR was 90.37% after 6 weeks of intervention. This finding is proportionate to comparable studies that determined the SFR of 65%–92% [2] , [39] , [40] , [41] , [42] , [47] , [48] , [49] , [50] . Moreover, the results were related to stone size; the highest SFR (100%) was achieved in stones <10 mm, and the lowest SFR (77.7%) in stones >30 mm ( p =0.0005).…”
Section: Discussionsupporting
confidence: 76%
“…From these results, we conclude that fluoroless FURSL is a safe and feasible procedure with high SFR and low morbidity compared to other studies [39] , [40] , [41] .…”
Section: Discussionsupporting
confidence: 49%
See 1 more Smart Citation
“…In another study, where RIRS was applied to patients including 62 (66.6%) males and 31 (33.3%) females with a mean age of 47.8 ± 14 years (range: 14-93), mean stone size was reported as 14.7 ± 5 mm (range: 7-32). In this study, an ureteral access sheet was used, and it was reported that fluoroscopy was not used in any of the cases and that no serious complications were encountered (18). In another study by Kirac et al, it was reported that a single dose was used to decrease the use of fluoroscopy when verifying the location of the ureteral access sheet (19).…”
Section: Discussionmentioning
confidence: 88%
“…Then doctor guide the catheter up through body to coronary arteries. Using X-ray 17,18 that called fluoroscopy, 19,20 video, and special dyes helps doctor to guide the catheter up into the blocked coronary artery. In the next step doctor pass a small wire through the catheter and then the next catheter that has a small balloon attached to it.…”
Section: Angioplastymentioning
confidence: 99%